2022
DOI: 10.3390/agriculture12122047
|View full text |Cite
|
Sign up to set email alerts
|

DFCANet: A Novel Lightweight Convolutional Neural Network Model for Corn Disease Identification

Abstract: The identification of corn leaf diseases in a real field environment faces several difficulties, such as complex background disturbances, variations and irregularities in the lesion areas, and large intra-class and small inter-class disparities. Traditional Convolutional Neural Network (CNN) models have a low recognition accuracy and a large number of parameters. In this study, a lightweight corn disease identification model called DFCANet (Double Fusion block with Coordinate Attention Network) is proposed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Meanwhile, CNNs have shown better recognition performance in datasets with simple backgrounds ( Ahila Priyadharshini et al., 2019 ; Lv et al., 2020 ; Yin et al., 2022 ), but the robustness of CNNs decreases when they are applied to corn disease identification in real environments ( Zeng et al., 2022a ). Moreover, our image dataset is similar to the studies of Chen et al. (2022) and Zeng et al.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, CNNs have shown better recognition performance in datasets with simple backgrounds ( Ahila Priyadharshini et al., 2019 ; Lv et al., 2020 ; Yin et al., 2022 ), but the robustness of CNNs decreases when they are applied to corn disease identification in real environments ( Zeng et al., 2022a ). Moreover, our image dataset is similar to the studies of Chen et al. (2022) and Zeng et al.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…Lin et al (2022a) proposed a lightweight CNN model called GrapeNet for recognizing specific grape diseases at different symptom stages, and the experimental results showed that the recognition accuracy for seven classes of grape diseases was 97.85%. Chen et al (2022) proposed a lightweight CNN model, DFCANet, for recognizing corn diseases in real environments, and the experimental results showed that the classification accuracy for six classes of corn diseases reached 98.47%.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition accuracy of the model is 98.5% on the open corn dataset with simple background and 95.86% on the local corn disease dataset with complex background. Chen Y. et al. (2022) proposed a lightweight corn disease recognition model called DFCANet, which relies on dual-feature fusion and downsampling module fusion of deep and shallow features, suppressing background noise and focusing on the lesion area.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, artificial intelligence (AI) based machine learning (ML) and deep learning (DL) techniques have played a vital part in the agricultural field, especially in the disease detection process [13,14]. Recently, ML-based techniques like k-nearest neighbor (KNN), multilayer perceptron (MLP), decision tree (DT), artificial neural network (ANN), and random forest (RF), and have been introduced in several studies to recognize crop leaf diseases effectually [15]. Despite the current practices performing well, there are limitations like low precision, high computational complexity, and deprived generalization ability.…”
Section: Introductionmentioning
confidence: 99%